PERAN LOKAL KONTEN DALAM PELESTARIAN BUDAYA MASYARAKAT DI DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA BATU - Ichsan Umardi, Maulana; Wicaksono, Moch. Fikriansyah (Jurnal Perpustakaan dan Informasi, 2025)
The rapid development of globalization through print and non-print media showcases a foreign culture that has resulted in a decrease in public awareness of local culture. This often happens in big cities in both developed and developing countries. Without preservation efforts from the government and public awareness, the existence of local culture will decline. The purpose of this research is to describe the role of local library content in efforts to preserve the culture of the Batu City community. The research method used is descriptive qualitative, with a single case approach. The theoretical basis used in this research is the function and purpose of the Library according to experts. Informants interviewed included the Library Coordinator, Librarian, and library users of Batu City Library. The data obtained was then analyzed using interactive data analysis techniques, namely data reduction, data presentation, and conclusion drawing. The results showed that local content plays an important role in preserving community culture in Batu City Library. Through local content, the library functions as a tool for recording local history and stories, strengthening cultural identity, preserving and developing cultural heritage, and ensuring the continuity of cultural knowledge from one generation to the next. However, the library faces several obstacles, such as a lack of proactivity and collaboration from local publishers, and low public interest in local content. To overcome these obstacles, the library has made various efforts, such as book review activities, storytelling competitions, and local content writing training in English. Through these initiatives, the library is trying to increase public appreciation and awareness of the importance of local content, as well as strengthen local cultural identity in the midst of globalization.